MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERORIENTASI PENGEMBANGAN KARAKTER BANGSA - Hidayat Hidayat (Fak. Tarbiyah UIN Maliki Malang, 2012)
Character of moral excellence or akhlaq is built upon various virtues which in turn has significant meaning when founded on values applicable in the national culture. Indonesian national character for the citizen is based on the measures assessed as a virtue constituted on the prevailing values ​​in society and the Indonesia as nation. Hence, the Education of National Character and Culture is directed on efforts in developing wisdom founding values so to mold the personality of citizens. The learning process of National Character and Culture Education deployed through an active learning process. Principally, value development is to be actively utilized by participant (as a self-subject of receiving, employing as self own and deploying the learnt values as basis of each action) therefore their position as active subjects in learning is the main principle of active learning. Thus both parts are necessary to each other.